Osteopororosis and reproductive health - Ristovski Kornić, Danijela; Matejić, Mirela (Archives of Pharmacy, 2025)
Osteoporosis is a prevalent issue among menopausal women; however, the number of women with risk factors across all age groups is increasing. This trend can lead to the development of osteopenia or osteoporosis at a younger age, significantly impacting women’s physical, emotional, and mental well-being. This review aims to evaluate the current literature on the prevalence of osteoporosis and its most common risk factors among women across all age groups. It serves as an updated reference for readers, helping to understand the fundamental pathophysiological mechanisms of the disease, diagnostic methods, and the role of medications and lifestyle in its prevention. Some authors suggest that the dominant mechanism of bone mass loss is slowed osteoblastic bone formation, while others highlight increased breakdown of the bone matrix as the more prominent mechanism of skeletal damage, depending on the underlying cause of osteoporosis. Increased bone fragility and a higher tendency towards pathological fractures significantly impact both the quality of life and life expectancy in women. Therefore, it is recommended that osteological screening and fracture risk assessment become a mandatory component of individualized care for women across all age groups. The focus of women’s bone health care has shifted from postmenopausal treatment to preventative care.
Keywords: osteoporosis; bone; menopause; prevention